1996
DOI: 10.1097/00006842-199609000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Psychosocial Factors and the Neuroendocrine Axis in Human Pregnancy

Abstract: The present findings are consistent with the premise that maternal-placental-fetal neuroendocrine parameters are significantly associated, both in magnitude and specificity, with features of maternal psychosocial functioning in pregnancy despite the systemic alterations associated with the endocrinology of pregnancy. These findings provide a basis for further investigations of the role of the neuroendocrine system as a putative mediating pathway between prenatal psychosocial factors and birth outcome, and poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(177 citation statements)
references
References 112 publications
7
162
1
7
Order By: Relevance
“…and their request for cesarean-section decreased (54). Inadequate childbirth-related training during pregnancy is one of the issues that should be taken into consideration.…”
Section: Fenwick Et Al (2009) Conducted a Study In Westernmentioning
confidence: 99%
“…and their request for cesarean-section decreased (54). Inadequate childbirth-related training during pregnancy is one of the issues that should be taken into consideration.…”
Section: Fenwick Et Al (2009) Conducted a Study In Westernmentioning
confidence: 99%
“…The forerunner of ACTH is the pro-hormone proopiomelanocortin (POMC), which is synthesized in various parts of the brain and other organs such as the intestine, the reproductive organs and also the placenta [23]. The most potent agonist for the secretion of ACTH is the CHR in the anterior pituitary gland.…”
Section: Clinical Syndromes In the Early Stages Of Life As A Results mentioning
confidence: 99%
“…The stress response mediated by glucocorticoids in the CNS, is done through the receptor type I and II. The type I plays an important role in modulating the response to the environment and the emotional stimuli, with changes in behaviour and the activity of the HPA axis [23]. The type II participates in the behaviour and neuroendocrine and autonomic response to stress [24].…”
Section: Interaction Between Maternal Stress and Preterm Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic stress and acute stress may exert different effects on fetal development and perinatal outcomes. Several authors have reported lower birth weight and shortened gestation in children born to mothers exposed to chronic stress compared to acute stress (Chrousos and Gold 1992;Rini et al 1999;Sable and Wilkinson 2000;Wadhwa et al 1996). Likewise, there is increasing evidence that exposure to forms of toxic stress in early life alters stress responses in adulthood.…”
Section: Chronic and Acute Stressmentioning
confidence: 99%